[PS 08-38] CLINICAL UTILITY OF OPTICAL COHERENCE TOMOGRAPHY (OCT) IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD). (September 2016) - Balmforth, Craig; Ruys, Titia; Cameron, James; Khei, May Hu; Kimmitt, Robert; Czopek, Alicja; Willox, Laura; Talwar, Dinesh; Dhillon, Baljean; Webb, David; Dhaun, Neeraj
Abstract : Objective: Chronic kidney disease (CKD) patients have a significantly increased risk of cardiovascular disease (CVD). An established association exists between vasculopathy in the kidney and eye, suggesting common pathophysiology. After correcting for CKD and classical CVD risk factors, retinopathy is associated with a higher prevalence of CVD. Optical coherence tomography (OCT) is a novel, non-invasive method of cross-sectionally imaging the retino-choroidal structures. Its use in CKD patients remains unexplored. Design and Method: We used the SPECTRALIS OCT in an exploratory study examining the retino-choroidal structures in 24 patients with hypertension, 24 with varying degrees of CKD and 25 matched healthy controls. Measurements included retinal thickness, retinal nerve fibre layer (RNFL) thickness, macular volume and choroidal thickness. Results: Retinal thickness was reduced across the outer 4 locations on the macula in CKD (p < 0.05). RNFL thickness did not differ between groups. Macular volume was lower in CKD compared to both hypertension (p < 0.0001) and health (p < 0.001). Similarly, CKD was associated with reduced choroidal compared to both hypertension (p < 0.001) and health (p < 0.01). In those with CKD, a thinner choroid was associated with a lower glomerular filtration rate (p < 0.01) and heavier proteinuria (p < 0.01), both important independent CVD risk factors. In CKD, a thinner choroid was also associated with increased plasma levels of systemic inflammatory markers (CRP, IL-6 and ET-1) and to the degree of renal histological injury. Conclusions: The decrease in retino-choroidal thickness in CKD may represent systemic microvascular injury. Thus, OCT could play a clinically significant role in assisting diagnosis of systemic microvascular disease, therapeutic intervention and identification of high-risk CVD patients.